Internet of Things: Security and Privacy standards - Adamova, A.; Zhukabayeva, T.; Ven-Tsen, Khu (Eurasian Journal of Applied Engineering and Technology (EJAET), 2023)
Ensuring security in the interaction of the Internet of Things (IoT) has focused the attention of many researchers. At present, the issue of standards is a very complex and important one that directly affects both the development and implementation of the Internet of Things in everyday life. There are many standards and protocols that may not be consistent across different layers of the architecture. This paper provides an overview of the current International Internet of Things Security Standards, which are discussed in various aspects such as terminology, architecture models, security and integration scenarios, classification and protocols. A comparative analysis of standards and related research is conducted to help inform decisions about the security of IoT systems during their development and production. This research aims to overcome the difficulties encountered and develop practical recommendations for the selection of controls and security of connected IoT devices. The research methodology included identification of gaps in IoT standards, analysis of existing problems and proposed solutions.